A SYSTEMATIC LITERATURE REVIEW ON THE DEVELOPMENT TRENDS IN MANAGEMENT ACCOUNTING RESEARCH - Husain, Fauziah; Dungga, Meriyana F.; Noholo, Sahmin (SYNTIFIC, 2024)
Background. The emergence of digital tools, such as data analytics and automation, enhances decision-making, aligns with sustainability, and supports strategic goals, especially in the context of achieving Sustainable Development Goals (SDGs) Research Purpose. The study aims to provide a comprehensive analysis of the developmental trends in management accounting by systematically reviewing recent literature. This review focuses on identifying key trends, existing gaps, and emerging themes to establish a framework for future research in this evolving field. ResearchMethod. Using a systematic literature review (SLR) approach, the research includes journal articles, conference proceedings, and reports published over the past decade. Articles were selected based on relevance to management accounting and sorted by topic, findings, and theoretical contributions. Findings. Key trends in management accounting include the integration of digital technology (e.g., AI, blockchain) for efficiency, accuracy, and improved decision-making, alongside a strong focus on environmental sustainability. The study also found significant interest in sustainability management practices, particularly regarding their role in meeting SDGs and enhancing corporate performance Conclusion. Management accounting is increasingly shaped by digitalization and sustainability imperatives. Technologies like AI and blockchain are reshaping data accuracy and efficiency, while sustainability practices encourage responsible business practices.